Rancang Bangun Instalasi Biogas Menggunakan Reaktor Fiber - Agung Prayetno Ismail; Siradjuddin Haluti; Hariadi Hariadi (Jurnal Teknologi Pertanian Gorontalo (JTPG), 2022)
Biogas is one of the energy sources that can be utilized by the community, especially for cooking. Biogas is more environmentally friendly than LPG gas that is generally used. This is because the source of biogas comes from animal manure or the like. This animal feces if not used will pollute the environment because of the unpleasant smell. Biogas is generally made from animal dung through an anaerobic fermentation process in a closed container at a certain time. In this study, biogas is made from cow dung and uses fiber as a fermentation container. In this study, biogas is made from cow dung and uses fiber as a fermentation container. The purpose of this study is to design biogas installations using fiber-type reactors. This research is based on the ease of raw materials, installation processes, and operation. The study was conducted through several stages, namely the design and making of installation drawings, preparation of the required tools and materials, design and fabrication, testing, data collection, and data analysis. Data was taken in this study in the form of pressure, flame tests, and its use to boil water. Testing and fermentation process of cow dung is carried out for 3 days. Based on the test results it is known that there was an increase in pressure during the fermentation process. During 3 days the fermentation process increased pressure to 11.5 cmHG, where the highest pressure on the third day was 15 cmHg. The results of the flame test at the final pressure show that the flame is blue for 27 minutes and 57 seconds. At a pressure of 11 cmHg, the flame began to dim. As for the 1L heating testing, water takes approximately 20 minutes and 3 seconds until the water boils.